Pengaturan Corporate Social Responsibility (CSR) Terhadap Perseroan Terbatas (PT) Dikabupaten Badung - Kadek Dedy Suryana (Universitas Mahendradatta, 2018)
Corporate Social Responsibility (CSR) is commitment of the company to contribute more to the public, either through social action as well as environmental responsibility. In Indonesia, the CSR now stated more emphatically again in limited liability company act (UUPT) article 74 no. 40 year 2007. Through his legislation, the industry or the corporations are obliged to do it, but this obligation is not a burden that is encumber. Badung Regency is a regency very rapid economic growth. Many companies both local, national and multi-national operating in Badung regency. The interaction between the company, the community and its influence on the social environment noticeably increased. Therefore, the regulation of CSR in Badung becomes important things to note from the government, businesses and people.Based on these descriptions, it is relevant to do a research study with the problem of whether the regulation of CSR in Badung Regency Regulation Number 6 Year 2013 About Corporate Social Responsibility is in conformity with Law Number 40 Year 2007 regarding Limited Liability Company? and as well as why CSR is required for the Company Limited in Badung to finance and facilitate local government programs ?. Of the problems that arise can be seen that this research is a type of normative legal research using the approach of legislation and approach to the concept.